Pengaruh NPF Terhadap Laba Bersih Bank Umum Syariah Tahun 2015-2019 - Imarotus Suaidah (Universitas Sains dan Teknologi Komputer, 2020)
This study aims to determine the effect of NPF on net income in Islamic commercial banks. This study uses a quantitative approach to the type of descriptive research. The population in this study was 14 Islamic commercial banks listed on the Indonesian stock exchange from 2015-2019, while the sampling technique used was purposive sampling. The data analysis method used is simple regression analysis to test the effect of NPF on net income. Before the simple regression test, a prerequisite analysis test was conducted, which consisted of a normality test and a homogeneity test. Based on the data analysis results, it can be seen that tcount is -3.084 and the significant value is 0.009 <0.05 so that there is an influence between NPF and net income. From the research results, it can be concluded that the NPF variable influences the net income of 37.8% of state-owned Islamic banks during the 2015-2019 period.